2021
DOI: 10.31729/jnma.6171
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Implant Removal in the Department of Orthopedics of a Tertiary Care Centre of Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Implant removal surgery is one of the common surgical procedures done in orthopedics. Studies report that a major portion of orthopedic surgeries carried out in different institutions comprises implant removal procedures. This can be challenging in limited manpower and infrastructure availability scenarios, like in developing countries like Nepal. This study aims to study the prevalence of orthopedic implant removal procedures carried out among overall surgical procedures in the orthopedic depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A descriptive cross-sectional study done at a tertiary care center found that implant removal surgery formed nearly one-fifth of the total orthopedic operations; implant removal was done as an elective procedure in 80% cases. More than 50% of patients undergoing implant removal were in the age group of 17 to 39 years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A descriptive cross-sectional study done at a tertiary care center found that implant removal surgery formed nearly one-fifth of the total orthopedic operations; implant removal was done as an elective procedure in 80% cases. More than 50% of patients undergoing implant removal were in the age group of 17 to 39 years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%